Threshold Functions for Modeling Gene Regulatory Networks - Kittaneh, Hadeel Ali (2024)
A Master of Science thesis in Mathematics by Hadeel Ali Kittaneh entitled, “Threshold Functions for Modeling Gene Regulatory Networks”, submitted in June 2024. Thesis advisor is Dr. Abdul Salam Jarrah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).